2017
DOI: 10.1016/j.clnu.2016.07.015
|View full text |Cite
|
Sign up to set email alerts
|

ESPEN guidelines on nutrition in cancer patients

Abstract: Cancers are among the leading causes of morbidity and mortality worldwide, and the number of new cases is expected to rise significantly over the next decades. At the same time, all types of cancer treatment, such as surgery, radiation therapy, and pharmacological therapies are improving in sophistication, precision and in the power to target specific characteristics of individual cancers. Thus, while many cancers may still not be cured they may be converted to chronic diseases. All of these treatments, howeve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

28
2,399
9
285

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 2,201 publications
(2,938 citation statements)
references
References 437 publications
28
2,399
9
285
Order By: Relevance
“…In addition, we found that the changes in SMM are not reflected by the observed changes in body weight. This is in agreement with previous studies that state that body weight and BMI are not appropriate tools to understand the effect of systemic treatment on body composition 4, 6…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In addition, we found that the changes in SMM are not reflected by the observed changes in body weight. This is in agreement with previous studies that state that body weight and BMI are not appropriate tools to understand the effect of systemic treatment on body composition 4, 6…”
Section: Discussionsupporting
confidence: 93%
“…The presence of malnutrition and weight loss in mCRC patients (which are present in up to 60% of patients) have been identified as risk factors for adverse events during these treatments and may limit the outcome of these treatments 2, 3. The most devastating syndrome in patients with cancer‐related malnutrition is cancer cachexia, which is defined as a progressive multifactorial syndrome characterized by an ongoing loss of skeletal muscle mass (SMM), with or without loss of fat, and which cannot be fully reversed by conventional nutritional support and leads to progressive functional impairment 4, 5. Cancer cachexia results from reduced food intake caused by a range of symptoms like anorexia, gastro‐intestinal symptoms, pain, and fatigue, occurring in combination with systemic inflammation and abnormal metabolism 4.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cancer is among the leading causes of morbidity and mortality throughout the world, and it is expected that the number of new cases will increase significantly in the next decades 1,2,3,4 . In Portugal, the incidence rate of new cases of malignant tumors has increased regularly, recording between 2009 and 2010 a 4% increase of cases 1 .…”
Section: Introductionmentioning
confidence: 99%